64 HYPOXIC VENTILATORY RESPONSE IN EARLY LUNG INJURY IS AUGMENTED BY OXYGEN-INDEPENDENT SENSITIZATION OF THE CAROTID BODY. (1st March 2006) - Jacono, F. J.; Peng, Y.; Nethery, D.; Faress, J. A.; Kern, J. A.; Prabhakar, N. R.
Abstract : Rationale: Acute lung injury alters ventilatory control by impairing gas exchange. However, even before hypoxemia develops, lung inflammation itself may alter ventilatory control. The objective of the present study was to examine the impact of acute lung injury on ventilatory control by hypoxia and hypercapnia. Methods: Experiments were performed on adult male Sprague-Dawley rats challenged with intratracheal injections of either bleomycin (BM; 1 unit) or PBS. Five days after the injections, the extent of lung injury was evaluated, and ventilatory responses to hypoxia (12% O2 ) or hypercapnia (7% CO2 ) were measured by plethysmography in unanesthetized animals and by diaphragmatic EMG in anesthetized animals. Contribution of carotid body sensory afferents to ventilatory patterns was evaluated by comparing responses before and after glomectomy in anesthetized animals. Results: BM-treated animals had increased total cell count, percent neutrophils, and protein levels in lavage fluid with no alterations in lung collagen content suggesting acute lung injury but not fibrosis. Core body temperature, PaO2, and PaCO2 were comparable between both groups of animals. In unanesthetized animals ( n = 16), baseline ventilation and the hypoxic ventilatory responses were significantly higher in BM-injected animals compared to control animals (average increases in minute ventilation [VE ]: BM +214 ± 59 mL/kg/min vs Control +60 ± 8 mL/kg/min; p = .003), whereas respiratory stimulation by hypercapnia was not altered to the same degree ( p = .672). The selective enhancement of hypoxic ventilatory drive was also present in anesthetized, spontaneously breathing animals ( n = 12) where average increases in respiratory rate [RR] were greater in animals with lung injury ( p = .036). In contrast, this difference between control and BM-exposed animals was abolished following bilateral glomectomy ( p = .786). In these same animals, average decreases in RR in response to sudden administration of hyperoxia (FiO2 change from 0.12'1.0) was significantly greater in the BM-exposed group compared to control animals (BM -13.0 ± 1.0 % vs control -9.7 ± 1.0 %; p = .041), and these differences were abolished following glomectomy ( p = .128). Conclusions: These data demonstrate that afferent sensory input from the carotid body contributes to a selective enhancement of hypoxic ventilatory drive in the absence of pulmonary fibrosis and arterial hypoxemia in early BM-induced lung injury.